Co-Seismic and Post-Seismic Temporal and Spatial Gravity Changes of the 2010 Mw 8.8 Maule Chile Earthquake Observed by GRACE and GRACE Follow-on - Wei Qu; Yaxi Han; Zhong Lu; Dongdong An; Qin Zhang; Yuan Gao (Remote Sensing, 2020)
The Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-on (GRACE-FO) satellites are important for studying regional gravitational field changes caused by strong earthquakes. In this study, we chose Chile, one of Earth’s most active seismic zones to explore the co-seismic and post-seismic gravitational field changes of the 2010 Mw 8.8 Maule earthquake based on longer-term GRACE and the newest GRACE-FO data. We calculated the first-order co-seismic gravity gradient changes (GGCs) and probed the geodynamic characteristics of the earthquake. The earthquake caused significant positive gravity change on the footwall and negative gravity changes on the hanging wall of the seismogenic fault. The time series of gravity changes at typical points all clearly revealed an abrupt change caused by the earthquake. The first-order northern co-seismic GGCs had a strong suppressive effect on the north-south strip error. GRACE-FO results showed that the latest post-seismic gravity changes had obvious inherited development characteristics, and that the west coast of Chile maybe still affected by the post-seismic effect. The cumulative gravity changes simulated based on viscoelastic dislocation model is approximately consistent with the longer-term GRACE and the newest GRACE-FO observations. Our results provide important reference for understanding temporal and spatial gravity variations associated with the co-seismic and post-seismic processes of the 2010 Maule earthquake.